An Experimental Investigation on Nano Coast as Bearing Liners - S.K. Mallik, K.; K.V. Ramana, Dr. (International Journal of Engineering and Technology, 2018)
Liners which are integral part of journal bearings, have a significant role on the life of a bearing. These are typically in the form of a bush, sleeve or a loop. Enhanced performance of a bearing liner with less cost is always acceptable. Coatings are the most preferable alternate for the existing bearing liners. Babbitt alloy is the one which is commonly used as bearing bush material. Tin, which is the significant material in the Babbitt is costly. In this work an experimental investigation has been taken-up by replacing Tin with Cadmium having similar mechanical and thermal properties as that of Tin but at the same time very less in cost. A nano coat of the alloy consisting of Antimony, Copper, Lead and Cadmium has been given on a mild steel specimen and experimented for Surface roughness and Hardness. The results are compared with Babbitt.Â Â